Current trends in the incidence of Urological malignancy at a tertiary level hospital in the northern part of Bangladesh - Arefin, Md Mashiur; Bari, Md Abdul; Islam, Md Tafiqul; Asaduzzaman, Md; Hossain, Homayra Tahseen; Chowdhury, Nurul Islam (Bangladesh Journal of Urology, 2023)
The second most common cause of death is malignancy. In clinical practice, genitourinary tumours are commonly encountered. Urological malignancies are raising due to increasing tobacco consumption, air and water pollution (arsenic, nitrate, chlorinated hydrocarbon) by unbalanced development, unhealthy diet, chronic infection, uncontrolled pesticides & fungicides used, food adulteration, using Chinese herbal products containing aristolochic acid, obesity and longer life expectancy. Over the past few years, advancement of diagnostic imaging, surgical technique, radiotherapy, chemotherapeutics and targeted agents have helped improve treatment outcomes. The incidence of urological malignancies is increasing like other malignancies in Bangladesh, which is poorly addressed. There is generally poor documentation of urological malignancies in Bangladesh. This study was carried out to document the pattern and distribution of urological malignancies in Rajshahi Medical College, Rajshahi, Bangladesh. Bangladesh J. Urol. 2022; 25(2): 98-105